The influence of temperature on tribological behaviour of Ni-SiC Electrodeposited coating. (3rd May 2016) - Fazel, M.; Bahramzadeh, S.; Garsivaz jazi, M. R.; Ramazani, M.; Bakhshi, S. R.
Abstract : In this article, the Electrodeposition of a Ni-SiC composite coating, which is mostly used as wear resistant coating in many applications, such as engine cylinders, combustion engines and casting moulds, was carried out from a sulphamate bath. Both mechanical and ultrasonic stirrers were used simultaneously during the process. Due to the working temperature of coating in the mentioned applications, the wear tests were carried out from 25 to 300 °C by pin-on-disk method and the high temperature tribological behaviour of the coating was investigated. Based on the results obtained from the wear tests, the Ni-SiC coating has low friction coefficient (0.36–0.42) and wear weight loss (0.7–2 mg) values at 25 and 100 °C. But, by increasing the temperature to 200–300 °C, which is near to the working temperature of many applications, the friction coefficient and wear weight loss values significantly increased.